THIN-WALLED FOUR-POINT CONTACT BALL BEARING CONTACT FINITE ELEMENT ANALYSIS - WU Li; YAO TingQiang; WANG LiHua; LIU XiaoBao (Jixie qiangdu)
Based on the ANSYS finite element software,the method of dividing the contact area of the four point contact ball bearing is proposed. Establish a uniform thin four point contact ball bearing 1/2 single rolling and ring and the bearing finite element model. Calculation and analysis of the grid cell size on contact characteristics of four point contact ball bearing accuracy influence and solve the bearing finite element model in the static radial force load distribution rules and obtained the thin-walled four point contact ball bearing,the more precise the elliptic contact area shape and four point connected contact state. Research shows that: for the calculation of the contact characteristics and the size of mesh generation approximate to 50 percent of the semi minor axis of the contact ellipse can get more precise results,for thin walled four point contact ball bearings,ball and the inner and outer rolling contact should force,the equivalent force and contact deformation and radial load is nonlinear ascending relationship,contact force and load distribution of the calculated results with the Hertz contact theory should be calculated values are in good agreement. The calculation results are more accurate to simulate the contact characteristics and load distribution of the thin wall four point contact ball bearing.